2013
DOI: 10.1364/ol.38.001869
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted material responses to nanosecond multiple-pulse laser damage: from statistical behavior to material modification

Abstract: This work is dedicated to the study of so-called fatigue effects upon nanosecond laser-induced damage of several crystalline materials and synthetic fused silica irradiated by multiple pulses. The obtained damage probability versus fluence and pulse number data are exploited to determine if the observed fatigue is due to statistics (the more often the material is irradiated, the higher the probability for it to be damaged) or to material modification under irradiation. Whereas 1064 nm irradiation seems to be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
(19 reference statements)
0
13
1
Order By: Relevance
“…The system was not injection seeded for these experiments because a check for reliable mono-mode operation on a pulse-to-pulse basis was not possible at 50 Hz pulse repetition rate. Moreover, previous experiments did not show an influence of longitudinal multi-mode operation [15]. .…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The system was not injection seeded for these experiments because a check for reliable mono-mode operation on a pulse-to-pulse basis was not possible at 50 Hz pulse repetition rate. Moreover, previous experiments did not show an influence of longitudinal multi-mode operation [15]. .…”
Section: Methodsmentioning
confidence: 77%
“…In a previous work [15], we described a method allowing to discriminate the two possible cases of fatigue encountered: statistical pseudo-fatigue, related to the fact that the higher the number of shots, the more probably the material will damage, and fatigue due to cumulative material modifications. Our study showed that synthetic fused silica (Suprasil 1) irradiated in the bulk showed a fatigue effect that was due to statistical pseudo-fatigue when irradiated at 1064 nm while the fatigue effect at 355 nm came from cumulative material modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Material modification fatigue is easily recognizable in the PðSÞ plots too, as they start in this case with a number of incubation pulses where the damage probability is zero. 14 Typically, this case is encountered when using UV wavelengths. More generally speaking, statistical fatigue is frequent if the laser-matter interaction is weak, whereas material modification fatigue is frequent if the laser-matter interaction is strong.…”
Section: Materials Modification Fatiguementioning
confidence: 99%
“…At infrared wavelengths, however, the damage probability as function of pulse number PðSÞ often follows a simple statistical model that assumes a constant single-pulse damage probability (and thus does not consider cumulative material modifications). 13,14 By the way, this statistical model has first been proposed in the early days of laser damage research by Bass and Barrett 15 and was abandoned later on (for a discussion, see Refs. 3 and 13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation